The Translation Flow of Arabic Novels into English Over Time - Fatima Alblooshi; Alaa Alasfour (Ars & Humanitas, 2023)
The discipline of Translation Studies has been criticized for being limited to only Euro-American perspectives and cultures, and thus scholars have called for expanding the scope of study beyond the Western conceptualizations of translation. This paper attempts to fill that void in the knowledge of the translation archaeology of Arabic novels translated into English. It creates an up-to-date bibliography of Arabic novels translated into English published worldwide across three decades (1988–2018) by consulting the US Library of Congress global union library catalogue and Goodreads. The collected materials are presented across two major historical periods: the post-Nobel Prize phase (1988–August 2001) and the post-9/11 phase (September 2001–2018). The bibliography includes 277 translated Arabic novels. It identifies the main actors involved in the process of translation, namely the authors, translators, and publishers. In addition to the quantitative analysis of this bibliographical data, this study adopts a comprehensive model by Allen (1995) to apply qualitative analysis to identify the topics being selected for translation into English. The study reveals that an increase in the number of translated works does not necessarily correlate with a greater understanding of the source text culture. In fact, increased translation flows can signal a reinforcement of known cultural stereotypes in the target culture.